PENGARUH DIMENSI CUSTOMER VALUE TERHADAP KEPUASAN PELANGGAN TRANSMART BANJARMASIN - Noor, Aris Setia; Lestari, Berta (INOVATOR, 2019)
This research was conducted to analyze the effect of customer value dimensions on TransMart customer satisfaction in Banjarmasin. The customer value variables used are value outcomes, process value and enjoyment shopping.               The type of research used is descriptive quantitative. The type of data used is qualitative and quantitative data, while the data sources are primary and secondary data. The population of this study is customers who shop at TransMart Banjarmasin. The sampling technique carried out for this study was determined intentionally. The number of samples taken is 30 customers. The technique of collecting data through observation and questionnaires. Data analysis techniques are carried out using multiple linear regression methods.